Non-Veneral Genital Dermatoses: A Study from Western Nepal - Ajay Kumar; Jenny Pun; Deepika Neupane; Saujan Subedi; Asim Mohammad; Brijesh Sathian (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The etiology of dermatoses involving genital areas could be venereal or on-venereal.  These disorders are responsible for mental distress and guilt which can be minimized by appropriate diagnosis and information to the patients.